2016
DOI: 10.1017/s0020818316000242
|View full text |Cite
|
Sign up to set email alerts
|

Peacekeeping, Compliance with International Norms, and Transactional Sex in Monrovia, Liberia

Abstract: United Nations policy forbids its peacekeepers and other personnel from engaging in transactional sex (the exchange of money, favors, or gifts for sex), but we find the behavior to be very common in our survey of Liberian women. Using satellite imagery and GPS locators, we randomly selected 1,381 households and randomly sampled 475 women between the ages of eighteen and thirty. Using an iPod in private to preserve the anonymity of their responses, these women answered sensitive questions about their sexual his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Peacekeeping has become the main method to manage and contain civil wars (Doyle and Sambanis 2000;Fortna 2008;Howard 2008). Although some question the effectiveness of peacekeeping missions pointing to incidents of abuse and sexual exploitation against local populations (Autesserre 2010;Barnett et al 2014;Beber et al 2017;Pouligny 2006), other studies suggest that PKOs promote peace and peacebuilding by strengthening the capacity of governments (Doyle and Sambanis 2000;Dorussen and Gizelis 2013). Empirical studies on peacekeeping so far have focused only on "negative"peace, or the absence of armed conflict, rather than "positive" peace including the well-being of civilians (Galtung 1964).…”
Section: Un Peacekeeping and Quality Of Peacementioning
confidence: 99%
“…Peacekeeping has become the main method to manage and contain civil wars (Doyle and Sambanis 2000;Fortna 2008;Howard 2008). Although some question the effectiveness of peacekeeping missions pointing to incidents of abuse and sexual exploitation against local populations (Autesserre 2010;Barnett et al 2014;Beber et al 2017;Pouligny 2006), other studies suggest that PKOs promote peace and peacebuilding by strengthening the capacity of governments (Doyle and Sambanis 2000;Dorussen and Gizelis 2013). Empirical studies on peacekeeping so far have focused only on "negative"peace, or the absence of armed conflict, rather than "positive" peace including the well-being of civilians (Galtung 1964).…”
Section: Un Peacekeeping and Quality Of Peacementioning
confidence: 99%
“…When the results of the survey were extrapolated to the Monrovian population at large, the researchers reported that their 'best estimate' was 'that about 58,000 women ages 18-30 in 2012 had engaged in transactional sex with U.N. personnel at some point.' 130 This is not to suggest that these studies have produced the 'correct' answer to the question of how widespread sexual exploitation and abuse by UN peacekeepers is. No doubt these findings could also be critiqued for their weaknesses, many predate the UN's reforms and there are obvious questions about the extent to which results for one mission or one group of victims or perpetrators would carry across to others.…”
Section: Statistics As Technologies Of Global Governancementioning
confidence: 99%
“…Risk factors positively associated with transactional sex included: low educational attainment, low income, increased duration of the relationship, early sexual debut, multiple sexual partners, and previous exposure to sexual violence. A second cross-sectional study in Liberia, this time in 2012, analyzed transactional sex specifically between Liberian women aged 18 to 30 and foreign military personnel deployed to the United Nations Mission in Liberia (UNMIL) (22). In this sample, 56% of Liberian women had engaged in transactional sex and 44% of these did so with peacekeepers.…”
Section: Prevalence Of Transactional Sexmentioning
confidence: 99%